Organizational Performance Index (OPI) Handbook: A practical guide to the OPI tool for practitioners and development professionals - Pact (Pact, 2015)
This handbook is intended to help development practitioners understand how to use and what can be achieved by Pact’s Organizational Performa nce Index (OPI) tool. This document will provide practitioners and man agers with information on how the Pact OPI works and how best to incor porate it in their country strategy or program.